Eugenol-Based Polymeric Materials-Antibacterial Activity and Applications - Anna Kowalewska; Kamila Majewska-Smolarek (MDPI AG, 2023)
Eugenol (4-Allyl-2-methoxy phenol) (EUG) is a plant-derived allyl chain-substituted guaiacol, widely known for its antimicrobial and anesthetic properties, as well as the ability to scavenge reactive oxygen species. It is typically used as a mixture with zinc oxide (ZOE) for the preparation of restorative tooth fillings and treatment of root canal infections. However, the high volatility of this insoluble-in-water component of natural essential oils can be an obstacle to its wider application. Moreover, molecular eugenol can be allergenic and even toxic if taken orally in high doses for long periods of time. Therefore, a growing interest in eugenol loading in polymeric materials (including the encapsulation of molecular eugenol and polymerization of EUG-derived monomers) has been noted recently. Such active macromolecular systems enhance the stability of eugenol action and potentially provide prolonged contact with pathogens without the undesired side effects of free EUG. In this review, we present an overview of methods leading to the formation of macromolecular derivatives of eugenol as well as the latest developments and further perspectives in their pharmacological and antimicrobial applications.